Prospective evaluation of gadoxetic acid magnetic resonance for the diagnosis of hepatocellular carcinoma in newly detected nodules ≤2 cm in cirrhosis. (28th May 2019) - Ayuso, Carmen; Forner, Alejandro; Darnell, Anna; Rimola, Jordi; García‐Criado, Ángeles; Bianchi, Luis; Vilana, Ramón; Oliveira, Rafael; Llarch, Neus; Bruix, Jordi
Abstract: Background and Aims: Most of the published studies about the diagnostic accuracy of gadoxetic acid‐enhanced magnetic resonance (EOB‐MR) for the non‐invasive diagnosis of hepatocellular carcinoma (HCC) have had a retrospective design. Thus, we aimed to prospectively evaluate the diagnostic accuracy of EOB‐MR for the non‐invasive diagnosis of HCC in nodules ≤2 cm detected by screening ultrasound (US) in patients with cirrhosis. Methods: Between July 2012 and October 2015, 62 consecutive asymptomatic Child‐Pugh A‐B cirrhotic patients with newly US‐detected solitary nodules between 1 and 2 cm were prospectively included in the study. Hepatic extracellular contrast‐enhanced MR (ECCE‐MR) followed by EOB‐MR were obtained in less than 1‐month interval. Two independent radiologists blindly reviewed the EOB‐MR studies, and the diagnosis of HCC was assigned when the lesion showed arterial enhancement followed by portal venous phase washout and/or hypointensity on the hepatobiliary phase (HBP). The final HCC diagnosis was made by ECCE‐MR according to the accepted non‐invasive criteria, or by biopsy in lesions with atypical vascular profile. Results: Final diagnoses were as follows: HCC (n = 41), intrahepatic cholangiocarcinoma (n = 2), colorectal metastases (n = 1) and benign conditions (n = 18). The sensitivity and specificity of EOB‐MR for HCC diagnosis were 56.1% (95% CI: 39.7‐71.5) and 90.5% (95% CI: 69.6‐98.8), respectively, while sensitivity of ECCE‐MR was 63.4% (95% CI: 46.9‐77.9). The low rate of hypointense HCCs in the HBP and suboptimal liver uptake of contrast agent justify the low sensitivity of EOB‐MR for HCC diagnosis. Conclusion: EOB‐MR does not surpass the diagnostic accuracy of ECCE‐MR for non‐invasive diagnosis of HCC in nodules ≤2 cm in cirrhotic patients.